2016
DOI: 10.14423/smj.0000000000000427
|View full text |Cite
|
Sign up to set email alerts
|

Utility of the Shock Index and Other Risk-Scoring Tools in Patients with Gastrointestinal Bleeding

Abstract: Patients with upper gastrointestinal (GI) bleeding frequently require hospitalization and have a mortality rate that ranges from 6% to 14%. These patients need rapid clinical assessment to determine the urgency of endoscopy and the need for endoscopic treatment. Risk-scoring tools, such as the Rockall score and the Glasgow-Blatchford score, are commonly used in this assessment. These tools clearly help identify high-risk patients but do not necessarily have good predictive value in identifying important outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 1 publication
1
10
0
Order By: Relevance
“…In the current study, the patient condition in both groups was quite similar before repeated hemostasis including the incidence of comorbid conditions, level of blood loss, shock index and coagulation status. There is evidence that in cases of severe gastrointestinal hemorrhage, the shock index is > 1 [ 30 ], complying with the data from our study where the median shock index was > 1 in both groups. Nevertheless, more studies are needed to acquire strong evidence.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the current study, the patient condition in both groups was quite similar before repeated hemostasis including the incidence of comorbid conditions, level of blood loss, shock index and coagulation status. There is evidence that in cases of severe gastrointestinal hemorrhage, the shock index is > 1 [ 30 ], complying with the data from our study where the median shock index was > 1 in both groups. Nevertheless, more studies are needed to acquire strong evidence.…”
Section: Discussionsupporting
confidence: 92%
“…The clinical Rockall score according to the author’s definition [ 28 ] has a maximum value of 7 points, and according to a recent study is sensitive in the prediction of mortality; however, the Glasgow-Blatchford score was more sensitive in the prediction of other outcomes, including the risk of re-bleeding [ 27 ]. Similar scoring systems were reported to be sensitive in the prognostication of high-risk patients and comparable with the Glasgow-Blatchford score when predicting in-patient mortality as well as predicting the need for endoscopic intervention [ 25 , 29 , 30 ] ( Table 7 ). Still, the Glasgow-Blatchford score and the Rockall score are superior considering their sensitivity in predicting the re-bleeding rate [ 8 , 24 ].…”
Section: Discussionmentioning
confidence: 80%
“…The SI can provide a comprehensive assessment of cardiovascular status and can be used to estimate the amount of blood loss and degree of shock (normal range: 0.5 to 0.7) [7]. A study by Rassameehiran et al showed that the SI was a good tool to identify patients with the potential for short-term adverse outcomes when they presented with upper gastrointestinal bleeding, and the SI was performed, as well as other risk-scoring tools, for gastrointestinal bleeding [22].…”
Section: Discussionmentioning
confidence: 99%
“…The shock index (SI) is the ratio of the heart rate to systolic blood pressure, and it is a clinical indicator of hemodynamic status. The SI can be used for the initial monitoring of patients with gastrointestinal bleeding and define treatment and provide an early warning of persistent bleeding or rebleeding after initial therapy [7]. Few studies have investigated the use of the SI in assessing upper gastrointestinal bleeding, and the relationship between the SI and other commonly used risk scores (e.g., the GBS) remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Using the hemoglobin values recorded on the patients' medical records before bleeding and at the time of UGIB diagnosis, we calculated each patient's estimated bleeding volume using Nadler's equation, which can enable assessment of the individual's total blood volume [14]. The SI was calculated by dividing the heart rate by the systolic blood pressure [15].…”
Section: Determination Of Upper Gastrointestinal Bleedingmentioning
confidence: 99%